Fifty shades of blue: Classification of music-evoked sadness. (March 2016) - Peltola, Henna-Riikka; Eerola, Tuomas
It has been repeatedly shown that sad music induces mainly pleasant or mixed emotions, and is particularly relevant for self-regulation goals. However, this is not entirely compatible with the view that sadness is one of the basic emotions experienced in the face of an unpleasant event or a loss. Also, a distinction between grief and sadness is often drawn, which seemingly does not have relevance in relation to musical experiences. The discrepancy between the positive accounts of emotions associated with sad music and those present in ordinary sadness may be related to the previously unacknowledged spectrum of affects associated with music-related sadness. The present study aims to expose the underlying affective experiences of music-related sadness. To examine this, a large qualitative data, consisting of open-ended answers from 363 participants, was subjected to thematic content analysis. The analysis revealed a range of emotions experienced which were classified into three themes: Grief, Melancholia, and Sweet sorrow . These themes differed depending on the valence of the overall experience and the contextual aspects. In addition, emotion induction mechanisms distinguished the themes and several previously unidentified types of affect regulation were observed. Variations in the ways people conceptualise sadness and music lead to differences in the affect regulation processes. In contrast to past research, the results suggest that truly negative emotions are relevant in association with music-related sadness. Dividing the music-evoked sadness into different categories of affective experiences helps to explain the current discrepancies and paradoxes surrounding sadness and music.